The Relationship Between Anxiety Level And Health Personnel Preventive Behavior In The Era Of The Covid-19 Pandemic In Padang Pasir Community Health Center, Padang City - Shanty Maria Lissanora Fernanda; Azis Mangara; Riska Wani Eka Putri Perangin-angin; Norong Perangin-angin (Jurnal EduHealth, 2023)
More than 1,500 health workers in the city of Padang have confirmed Covid-19. At the Padang Pasir Health Center from June 2020 to July 2022, there were 47 health workers and 36 family members who were confirmed to have COVID-19. Preventive behavior carried out by health workers during the Covid19 pandemic, by implementing the 3M strategy: wearing masks, maintaining distance and washing hands, implementing Infection Prevention and Control (PPI). Anxiety felt by health workers while working during the Covid-19 pandemic, decreased stamina, increased work demands and an uncomfortable work environment because many were confirmed by Covid-19. The purpose of the study, the relationship between anxiety levels and preventive behavior of health workers in the era of the Covid-19 pandemic at the Padang Pasir Public Health Center, Padang City. This type of research, quantitative with analytical descriptive method through a cross-sectional approach. The results of the study, from 83 respondents, there was the highest score on the moderate level of anxiety (26.5%) of the respondents, and the highest score on the good preventive behavior (57.8%) of the respondents. The results of the Chi-Square statistical test obtaineda p value of 0.029 (p 0.05), it is known that there is a relationship between anxiety levels and preventive behavior of health workers during the Covid-19 pandemic era at the Padang Pasir Public Health Center, Padang City. Suggestions, it is hoped that health workers carry out preventive behavior, in carrying out services, especially during the Covid-19 pandemic.